2008
DOI: 10.1016/j.ejcts.2007.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic assisted venous drainage for orthotopic heart transplantation in patients under mechanical circulatory support: a double-edged sword

Abstract: Background: Heart transplantation in patients supported with ventricular assist devices (VADs) entails a high risk of injury at resternotomy. Prior femorofemoral bypass is the preferred approach in these patients, but poor venous drainage may restrict arterial flow rate. Patients and methods: We compared bypass parameters, transfusion requirements and postoperative outcome in 33 consecutive patients (40.4 AE 12.2 years old, 28 men) assisted with the Thoratec W paracorporeal VAD (mean duration, 3.0 AE 2.96 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…18,19 However, at negative pressures up to −40 mm Hg, there was no difference compared to drainage by gravity. 20 Similar reports are available for the clinical setting, 21 where not only additional gaseous embolic load but also excessive hemolysis are an issue, 21 a phenomenon being also known for a long time. 22 This latter concern has proven to be unfounded for the stent-type design of the virtually wall-less cannulas studied here as demonstrated previously for its use in combination with gravity drainage 6,23 as well as with augmented venous drainage.…”
Section: Discussionmentioning
confidence: 88%
“…18,19 However, at negative pressures up to −40 mm Hg, there was no difference compared to drainage by gravity. 20 Similar reports are available for the clinical setting, 21 where not only additional gaseous embolic load but also excessive hemolysis are an issue, 21 a phenomenon being also known for a long time. 22 This latter concern has proven to be unfounded for the stent-type design of the virtually wall-less cannulas studied here as demonstrated previously for its use in combination with gravity drainage 6,23 as well as with augmented venous drainage.…”
Section: Discussionmentioning
confidence: 88%
“…Although some in vitro studies found a correlation between the augmented venous drainage with either a vacuum or a centrifugal pump as well as the incidence of micro-embolism in the arterial line [ 15 , 16 ] at a negative pressure up to −40 mmHg, there were no differences compared to gravity venous drainage, especially in the clinical setting [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 Thus, improved venous drainage has the potential to simplify the surgical procedure. 2 While poor drainage is a concern, excessive drainage may also problematic, 3 as it leads to a collapse of the venous wall around the end of the venous cannula and/or its orifices; this collapse phenomenon is called "chattering" or "fluttering, " and it results in intermittent interruption and overall reduction of venous drainage. Hydrodynamic analysis of venous cannulas on a bench is a valuable technique to evaluate their performance during CPB.…”
Section: Introductionmentioning
confidence: 99%